Development in Cape Town's Central Business District : the office component - Rideout, Timothy William (University of Cape Town, 2016)
Bibliography: pages 226-229. === The first part of the thesis covers the background to the research, namely (a) a selective review of previous work in the field of office development and location studies and the subsequent identification of the objectives of the present research, (b) a summary of the historical development of the central area of the City of Cape Town, (c) the definition of the study area, this being the Central Business District of the city of Cape Town and (d) a discussion of the collection of land use and gross floor area data, the identification and resolution of problems in the data and the administering of a postal Questionnaire to 1,400 office establishments in the CBD. This section also covers the problem of identifying and delimiting land use clusters. The technique selected for use in such delimitation was that developed by D. H. Davies (1965) augmented by the development of three 'indices of clustering '. The second part of the thesis presents, by means of thirty-three detailed maps, a comprehensive analysis of office land use patterns in the Cape Town CBD in 1983. Clusters are indicated according to the Davies technique. It was found that many office functions exhibited clustering in distinct parts of the CBD and, moreover, certain functions appeared to show close similarities in their respective location patterns. A factor analysis identified six groups of similarly located land uses, on which basis a model of the spatial organization of the CED was proposed. Data, derived from the postal questionnaire, on the characteristics and requirements of individual office functions was used to explain the location patterns. Previous studies have usually considered linkages as being the primary locational determinant for the office sector, but in this case it was found that clustering and the existence of similar location patterns between office functions usually arose from a combination of common locational requirements. The major locational determinants were found to be the rent paying ability of establishments, the relative importance of the accessibility of the establishment to either general public or commercial clients, the existence of strong linkages with other functions (especially where such functions were eccentrically located with respect to the CBD, such as the Docks) and in some cases the importance of occupying prestige premises. The comparatively minor role of linkages with other functions was considered to be a reflection of the relatively small size of the CBD. The thesis concludes with a study of past trends and future projections of the development of the CBD. The growing dominance of the office sector is clearly revealed, as is the effect of the Foreshore Reclamation Scheme in promoting a northward migration of the Office Core while leaving the Retail Core largely unchanged from its 1957 location. On the basis of current development projects it was projected that there would be considerable short-term vacancy in the office sector by late 1986. In the longer term, though, gross floor area requirements for all uses are predicted to rise by almost 50% to 3.475 million square metres by the year 2000. Such development of all of the space currently permitted by the Town Planning Scheme raises the possibility of space shortages and the loss of remaining historic buildings.